The concept of informal care: ambiguities and controversies on its scientific and political uses - Cruz, Sofia Alexandra; Soeiro, José; Canha, Sara; Perrotta, Valentina (Frontiers in Sociology, 2023)
Starting from an analysis of the scientific and political uses of the concept of informal care, this paper raises questions and launches the debate on the causes and effects of its uses.Recognising the diversity and the contradictions found across the use of the term, it explains how its predominant use in Europe can be problematic. First, although it is widely recognised that care is provided primarily by women, this gender dimension is not emphasised in a concept that obscures the sexual division. Second, it does not render explicit that informal care is work, despite being unpaid. Third, the allusion to informality is likely to generate confusion with informal employment of care workers. Finally, studies often focus exclusively on care provided by family members, without distinguishing the spaces in which the work takes place and the social relationships it involves, namely the family or community. In Europe, where documents from (non)governmental organisations focus mainly on long-term care related to demographic ageing, it is the care crisis of formal care provision systems, faced with financial fragility, reduction in funds and insufficient supply to meet the demand, that brings informal care to the political and scientific agendas. This paper argues that it is necessary to define conceptual boundaries that allow international studies on the dimension and value of this care work to be compared. It also advocates the importance of making visible that this is work, unpaid and female-dominated, since this view supports action guidelines more focused on social transformation and empowerment.